Lactic Acid Production From Cocoa Pod Husk by Studying Further the Influence of Alkaloids on Fermentation Process using Lactobacillus Plantarum Bacteria - Dodi Irwanto; W. Wiratni; R. Rochmadi; Siti Syamsiah (Reaktor, 2018)
Cocoa Pod Husk (CPH) is the biomass waste from cocoa industry, generated after the digestion process. It accounts for about 70-75% of the cocoa fresh fruit. CPH contains active compounds of alkaloids that are thought to be the inhibitors of the lactic acid fermentation process using microorganisms. This study aims to produce Lactic Acid from CPH by studying further the influence of alkaloids on fermentation process using Lactobacillus plantarum bacteria. Fermentation using Lactobacillus plantarum bacteria was carried out at 50°C and with agitation at 100 rpm in incubator shaker for 48 h. This process was conducted to determine the effect of the addition of alkaloids by analyzing through the comparison between the consumption of substrate (glucose), dry weight of the cell, and the production of lactic acid. Evaluation of the differences in the performance of microorganisms at various treatments was performed based on the parameters values of the kinetic models prepared for the case studied. The kinetic model fitting results showed that the presence of alkaloids alters the growth patterns of products from growth-associated products into mixed patterns because the products were formed during slow growth and stationary phases. The maximum growth rate (μm) and substrate inhibition constant (Ks) obtained on each variation of inhibitor addition were likely to remain constant at the values of 0.69 h-1 and 3.89 g/L respectively, as these parameters were unaffected by the addition of inhibitor